Final results of a dose escalation protocol of stereotactic body radiotherapy for poor surgical candidates with localized renal cell carcinoma. (February 2021) - Grubb, William R.; Ponsky, Lee; Lo, Simon S.; Kharouta, Michael; Traughber, Bryan; Sandstrom, Kate; MacLennan, Gregory T.; Shankar, Eswar; Gupta, Sanjay; Machtay, Mitchell; Ellis, Rodney J.
Highlights: SBRT for localized RCC is a promising treatment modality especially in poor surgical candidates. Dose escalation from 48 - 60 Gy in 3 fractions was achieved with zero dose-limiting toxicities. Local control following treatment was 90% at 3 years. Interpretation of post-SBRT biopsies remains uncertain. Studies comparing SBRT to percutaneous ablation for poor surgical candidates are warranted. Abstract: Background and purpose: We previously demonstrated the safety of doses up to 48 Gy in 4 fractions with stereotactic body radiotherapy (SBRT) in poor surgical candidates with localized renal cell carcinoma (RCC). In an additional expansion cohort, we aimed to assess the safety of further dose escalation to 48–60 Gy in 3 fractions. Material and methods: Patients were required to have localized RCC and be poor surgical candidates due to medical comorbidities. Dose-limiting toxicity (DLT) was defined as acute (<180 days) grade ≥3 gastrointestinal/genitourinary toxicity by CTCAEv4. Tumor response was assessed using RECIST 1.1 criteria measurements every 6 months for 3 years and optional percutaneous biopsy. Results: Groups of 4, 4, and 3 patients received 48, 54, and 60 Gy in 3 fractions, respectively from 2012 to 2016. Median follow-up was 34.3 months. Zero DLTs were observed. Acute toxicities were limited to grade 1 fatigue and nausea in 45.5% and 18.1%. Late grade 2+ and grade 3+ possibly treatment-related events occurred in 18.1% and 9.1%, respectively. Three-year local control was 90% by RECIST 1.1 criteria. Five of 5 post-treatment biopsies in the expansion cohort were positive by Hematoxylin and Eosin staining. Three of the 5 patients with positive biopsies have been observed for 1.2–3.9 years without evidence of progression. Conclusion: Dose escalation to 60 Gy in 3 fractions was achieved without DLTs. Favorable local control rates were observed, and the interpretation of post-SBRT biopsies remains uncertain. Further studies comparing SBRT to percutaneous ablation for poor surgical candidates with RCC are warranted.